PREVALENCE OF URINARY TRACT INFECTION AND ASSOCIATED FACTORS AMONG PREGNANT WOMEN ATTENDING THE UNIVERSITY TEACHING HOSPITAL OF KIGALI, RWANDA - Hakizuwiteka Valens, Dr. Mojeed Akorede Gbadamosi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Urinary tract infections (UTIs) are prevalent globally, particularly during pregnancy, affecting both the bladder and kidneys. This study focuses on UTI occurrence among pregnant women at Kigali University Teaching Hospital (CHUK). Understanding this issue is vital for developing effective strategies with the Ministry of Health to prevent and treat these infections. UTIs are a major health concern in sub-Saharan Africa, but research on their prevalence and related factors among pregnant women in Rwanda is sparse. Aim: The general objective of this study is to assess the prevalence and associated factors of urinary tract infections among women obtaining care at University Teaching Hospital of Kigali, Rwanda from January 2022 to January 2023. Materials and Methods: A retrospective analysis of patient files was conducted from January 2022 to January 2023 for all females aged 18 to 45 who were pregnant during that period. Data were extracted and analyzed using SPSS version 28 software. The prevalence of UTIs was determined using frequency and proportion. Factors associated with UTIs were identified using binary logistic regression techniques, with statistical significance set at two-tailed p-values below 0.05. Results: The study found that among 350 pregnant women attending CHUK, 53 were diagnosed with UTIs, resulting in a prevalence rate of 15.1%. The second trimester showed a significantly lower odds ratio (AOR=0.53, 95% CI 0.34-0.88) compared to the first trimester, suggesting a protective effect. The third trimester did not significantly differ from the first trimester (AOR=0.67, 95% CI 0.32-1.08). Urinary tract abnormalities were not significantly associated with UTI prevalence (AOR=0.90, 95% CI 0.77-1.28). However, a history of UTI, diabetes, HIV status, and a weakened immune system were significantly associated with UTI prevalence. While the frequency or adequacy of antenatal care visits and urinary catheterization showed potential associations with UTI prevalence, these were not statistically significant. Discussions: The study at CHUK highlighted the need to assess UTI prevalence among pregnant women to aid effective Ministry of Health strategies. It revealed a 15.1% UTI prevalence among 350 participants. The second trimester showed lower odds of UTIs compared to the first, suggesting a protective effect, while the third trimester did not differ significantly. No significant association was found between urinary tract abnormalities and UTI prevalence. Significant factors contributing to UTI prevalence included history of UTI, diabetes, HIV status, and weakened immune system. Antenatal care visit frequency, urinary catheterization, and related procedures also showed potential links to UTI prevalence. Conclusion: The study identified a strong association between demographic, maternal, health-related, and health facility factors and the prevalence of UTIs among pregnant women at CHUK, Rwanda. It recommended that the Ministry of Health implement nationwide education and screening programs for pregnant women to raise awareness about UTIs and their risk factors.